Uma estratégia para auxiliar na distribuição da etapa de especificação de requisitos em desenvolvimento distribuído de software - Matusse, Euclides Alfredo (2013)
Distributed development of software (DSD) has been an approach increasingly adopted by companies. However, rnanaging the distribution of steps in a process of development among distributed teams bring chailenges regarding elements that could be considered. Thus, define strategies that consider socio technical aspects involving people, process and technology can provide the necessary support. This dissertation presents a strategy to support the project manager during the activity distribution the requirements specification stage. It considers two aspects: (1) identify and analyze a set of metrics that take into account the requirements specification stage in DDS , in order to find evidence that these metrics can be used as indicators, and (2) develop a strategy for defining indicators for the distribution requirements specification stage in DSD using metrics. So, the metric effort estimation was considered. Also, (co) relationship between effort and metrics related to factors of communication were established. To evaluate the effort estimation and correlation established we use the Goal Question Metric (GQM). Besides these, metrics considering geographical and temporal distance between the teams were considered .An experiment considering three globally distributed teams, characterizing the offshore outsourcing model was also carried out . The results of the experiment show evidence that such metrics can be used as appropriated indicators to aliocate the requirements specification. stage in model offshore outsourcing.